Efficacy and safety of bismuth‐based quadruple therapy for Helicobacterpylori eradication in children. Issue 4 (7th June 2021) - Kotilea, Kallirroi; Cadranel, Samy; Salame, Assaad; Nguyen, Julie; Mahler, Tania; Miendje Deyi, Véronique Yvette; Verset, Laurine; Bontems, Patrick
Abstract: Objectives: To evaluate the efficacy and safety of a 10‐day quadruple therapy containing colloidal bismuth sub‐citrate (CBS), esomeprazole (ESO), amoxicillin (AMO), and metronidazole (MET) for Helicobacter pylori ( H . pylori ) eradication in children. Methods: Monocentric, open‐label, prospective, single‐arm clinical trial in children aged 6–17 years with H . pylori infection. The study was carried out on consecutive patients with upper gastrointestinal symptoms and H . pylori infection confirmed by histology and culture of gastric biopsies. The outcome was evaluated using a 13 C‐urea breath test 8–10 weeks post‐therapy. Adverse events and compliance were evaluated by daily journal and pill counting. Results: A total of 36 children fulfilling the inclusion criteria were enrolled. Eight (22.2%) of them had a prior H . pylori eradication treatment. Thirteen (36.1%) patients were infected by a strain resistant to MET and 8 (22.2%) by a strain resistant to both MET and Clarithromycin (CLA). In the intention‐to‐treat population (ITT), eradication was achieved in 35/36 patients ( 95%CI : 85%−99% ). Twenty‐three children reported at least one adverse event (63.8%), mostly mild (nausea, vomiting, abdominal pain, diarrhea, dark stool, metallic taste, headache, and rash). The compliance rate was high, with 30 (83.3%) patients taking >90% of the treatment. Conclusion: 10‐day quadruple therapy containing CBS, ESO, AMO, and MET for H . pylori eradication in children is a safe and very effective solution, especially for previously treated patients and those infected with double resistant strains.